2008
DOI: 10.1086/526489
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Parameters of Field L and T Dwarfs1

Abstract: We present an analysis of the 0.95Y14.5 m spectral energy distributions of nine field ultracool dwarfs with spectral types ranging from L1 to T4.5. Effective temperatures, gravities, and condensate cloud sedimentation efficiencies are derived by comparing the data to synthetic spectra computed from atmospheric models that self-consistently include the formation of condensate clouds. Overall, the model spectra fit the data well, although the agreement at some wavelengths remains poor due to remaining inadequaci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
451
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(488 citation statements)
references
References 94 publications
32
451
5
Order By: Relevance
“…For each candidate spectrum, we determine the best fit in spectral type and extinction by minimizing a goodness-of-fit statistic between the candidate and each template (Cushing et al 2008), defined as…”
Section: Fitting Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…For each candidate spectrum, we determine the best fit in spectral type and extinction by minimizing a goodness-of-fit statistic between the candidate and each template (Cushing et al 2008), defined as…”
Section: Fitting Techniquementioning
confidence: 99%
“…where w λ is the weight of each spectral element (taken as its spectral width as in Cushing et al 2008), f λ and F λ are the flux densities of the candidate and template, respectively, and σ λ is the noise for the candidate spectrum. Regions of the spectra dominated by telluric absorption were excluded from the fit, which was done over the wavelength ranges 1.45−1.8 and 2−2.45 μm.…”
Section: Fitting Techniquementioning
confidence: 99%
“…This is likely due to the presence of remnants of dust clouds, floating around in upper layers, that are not included in the modelled spectra (see Ruiz et al 1997;Ackerman & Marley 2001;Burgasser et al 2002b;Burrows et al 2006;Cooper et al 2003;Helling et al 2008). Cushing et al (2008) have computed the properties of SDSSp J125453.90-012247.4 and 2MASS J05591914-1404488 from the comparison of low and intermediate resolution spectra in the 0.95-14.5 μm wavelength range and synthetic spectra. They found that SDSSp J125453.90-012247.4 has condensate clouds that are thicker than those in 2MASS J05591914-1404488, which may explain the difference in the spectra of these overluminous T dwarfs.…”
Section: Modelled and Observed Spectramentioning
confidence: 99%
“…Most modelling efforts on T dwarfs have concentrated on fitting broad-band colors and low-resolution spectra, and deriving atmospheric parameters by comparing the data with synthetic spectra (Cushing et al 2008;Leggett et al 2007;Saumon et al 2007Saumon et al , 2006Burgasser et al 2006b;Tsuji et al 2005Tsuji et al , 2004Burgasser et al 2004). Martín & Zapatero Osorio (2003) estimated the surface gravity and effective temperature of one Article published by EDP Sciences T dwarf from a mid-resolution near-infrared spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of model predictions to the spectra of empirical benchmarks (sources with astrometric distance and bolometric luminosity measurements, companions to nearby stars, resolved binary systems) have shown that these features are linked to both surface gravity and metallicity variations , Liu et al 2006Burgasser et al 20007;Cushing et al 2008;Looper et al 2008). High-angular resolution imaging and spectral template analyses have verified these effects as intrinsic to the evolution of brown dwarfs across the L/T transition and not the result of age or metallicity variations Liu et.al 2006;Looper et al2008).…”
Section: Secondary Parametersmentioning
confidence: 99%